Data Visualization And Sales Prediction of PD. Asia Agung (Ajinomoto) Pontianak in 2019 - Willy Yunus; Ririn Ikana Desanti; Wella Wella (IJNMT (International Journal of New Media Technology), 2020)
PD. Asia Agung Pontianak is the only official distributor of Ajinomoto in the West Kalimantan region. Every year this company needs to find out the amount of turnover that will be obtained in the coming year. Unfortunately, the company only makes predictions using the average income from each year which is very less accurate. This research is conduct to create visualizations and predictions using multiple linear regression methods to predict the turnover obtained in the coming year. Multiple linear regression is a regression analysis method that can use more than 2 variables in the prediction process which is divided into 2 parts, namely the dependent variable and the independent variable. The results obtained in this research are prediction results in 2019 using data from 2010 to 2018 as a basis. Prediction results show that the longer the data used the smaller the error rate obtained. The original data from the company is visualized using a dashboard on tableau software so that the data could be easier to analyze by the company.